2019
DOI: 10.1111/jipb.12848
|View full text |Cite
|
Sign up to set email alerts
|

Production of very‐high‐amylose cassava by post‐transcriptional silencing of branching enzyme genes

Abstract: High amylose starch can be produced by plants deficient in the function of branching enzymes (BEs). Here we report the production of transgenic cassava (Manihot esculenta Crantz) with starches containing up to 50% amylose due to the constitutive expression of hair-pin dsRNAs targeting the BE1 or BE2 genes. All BE1-RNAi plant lines (BE1i) and BE2-RNAi plant lines (BE2i) were grown up in the field, but with reduced total biomass production. Considerably high amylose content in the storage roots of BE2i plant lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 75 publications
(103 reference statements)
2
21
0
1
Order By: Relevance
“…SBE transcriptional changes paralleled changes in the amylopectin to amylose ratio in developing cassava roots, while the amylopectin-to-amylose ratio remains constant during potato tuber development. Cassava root starch quantity and quality, sugar content, and relative SBE expression were summarized from four publications [ 81 , 137 , 143 , 144 ]. Potato tuber starch content and composition, relative SBE transcript expression during tuber development were adapted from [ 145 , 146 ], and the cold storage changes were adapted from [ 147 ].…”
Section: Putative Role Of Sbes As Determinants Of Postharvest Quality In Horticultural Cropsmentioning
confidence: 99%
“…SBE transcriptional changes paralleled changes in the amylopectin to amylose ratio in developing cassava roots, while the amylopectin-to-amylose ratio remains constant during potato tuber development. Cassava root starch quantity and quality, sugar content, and relative SBE expression were summarized from four publications [ 81 , 137 , 143 , 144 ]. Potato tuber starch content and composition, relative SBE transcript expression during tuber development were adapted from [ 145 , 146 ], and the cold storage changes were adapted from [ 147 ].…”
Section: Putative Role Of Sbes As Determinants Of Postharvest Quality In Horticultural Cropsmentioning
confidence: 99%
“…First, we obtained polyclonal antibodies specific for cassava MeSSI, MeSSII, MeSBEI, MeSBEII, MeISAI, MeISAII and MeGBSSI by means of recombinant protein immunization. Genetic tests to verify the specificity of each antiserum by using RNAi transgenic plants including SSC-6, sbe1 (Zhou, Zhao et al 2020), sbe2 (Zhou, Zhao et al 2020) and gbss1 (Zhao, Dufour et al 2011), which inhibit expression levels of MeSSII, MeSBEI, MeSBEII and MeGBSSI , respectively. The results demonstrate conclusively that all these antibodies had good specificity and could specifically recognize the corresponding proteins (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that the cassava GBSSI promoter is the best candidate to achieve tuberous root-specific expression in cassava (Koehorst-van Putten et al, 2012a). Recent research conducted by team of Chinese Academy of Sciences (CAS) successfully produced high amylose transgenic cassava by down regulating BE genes, which are responsible for amylopectin biosynthesis (Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…It is therefore, suggested to employ other gene construct and other mechanism to obtain better growth and yield of cassava, which have been improved by Bull et al (2018) and Zhang et al (2019) using CRISPR/Cas9 gene editing. Zhou et al (2020) produced transgenic cassava with starches containing up to 50 % amylose due to the constitutive expression of hair-pin dsRNAs targeting the BE1 or BE2 genes. The generation of high-amylose cassava was obtained by the group by down-regulating expression of the BE2 gene.…”
Section: Yield Performance and Amylose Content Of High Amylose Transgenic Adira 4 Grown In The Screenhousementioning
confidence: 99%